Penggalian Potensi Usaha BUMK Hendro Mulyo, Lampung Tengah - Kurnianingsih, Puji; Syuja, Andika Fadila; Adi, Fahrizal; Prihandini, Nabilla Ulfah; Kurniawan, Reza; Sari, Saraswati Permita; Raharjo, Taufik; Sulaeman, Agus Sunarya (Journal Pemberdayaan Masyarakat Indonesia, 2019)
The Village Owned Enterprises (BUMK) Hendro Mulyo was established by the Government of Tempuran Village, Trimurjo District, Central Lampung Regency. Although it is strategically located, BUMK has not been able to explore business potential following the conditions of the local community. The purpose of this community service activity is to explore the potential of the village as a form of BUMK business and make a Budget Plan for BUMK businesses. The result of community service activities is that BUMK management has established a business form and can plan their business budget.